Development of Physics Learning Media with POE Model-Based Corrective Feedback for Senior High School - Afina Maulidiani Rahma; Muhammad Reyza Arief Taqwa; Nugroho Adi Pramono (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2020)
This research was conducted with the aim of describing web-assisted physics learning media with POE model-based corrective feedback and describing the appropriateness and legibility of the product. This type of research is research and development (R & D) with the 4D models. Development 4D model has 4 steps that are defined, design, development, and disseminate, but this development did up to the development step. The data analysis techniques used were qualitative and quantitative. Qualitative data is obtained from comments and suggestions from expert validators, while quantitative data is obtained from the total score of the assessment based on the Likert scale 1-4. At the validation test and product legibility done by the physics lecture of State University of Malang and physics teacher of Senior High School 1 Kedungwaru as limited trial respondent. Based on the validation test conducted, it was obtained an average value of 3.56 with a very valid category, while for limited trials an average percentage of 83.3% was obtained with legible criteria. Thus the web-assisted physics learning media developed is declared valid and suitable for use.